Expectations and preferences for palliative chemotherapy in head and neck cancers patients. (December 2016) - Patil, Vijay; Joshi, Amit; Noronha, Vanita; Deodhar, Jayita; Bhattacharjee, Atanu; Dhumal, Sachin; Chandrakanth, M.V.K.; Karpe, Ashay; Talreja, Vikas; Chandrasekharan, Arun; Turkar, Siddharth; Ramaswamy, Anant; et al.
Highlights: Prolonging life was a primary expectation from chemotherapy in 41% of patients. Symptom relief was an expectation from chemotherapy in 58.5% of patients. Minimum increment in life expected from palliative chemotherapy is 1 year. Preferred location of stay post diagnosis was home in majority patients. Abstract: Background: Head and neck cancer patients undergoing palliative chemotherapy have a limited overall survival. Expectations and preferences of such patients towards palliative chemotherapy after explanation of disease prognosis and treatment options are unknown. Methods: This was a single arm, prospective, observational study where newly diagnosed head and neck cancer patients warranting palliative chemotherapy underwent protocol defined counselling. Following counselling, they were administered chemotherapy expectation and preference proforma (CEP). The primary objective of this study was to estimate the percentage of patients opting for an increase in survival as the primary expectation from chemotherapy. Results: We recruited two hundred patients all patients except one answered the CEP. Prolongation of life as the primary expectation from palliative chemotherapy was seen only in 82 patients (41.0%; 95% CI 34.4–47.9%). Symptom relief was the primary expectation or an equally important expectation amongst the remaining 117 patients (58.5%; 95% CI 51.6–65.1%). There was a statistically significant difference between the preferences of patients having a primary expectation of prolongation of life as opposed to symptom relief regarding the minimum expected number of patients need to treat to get prolongation of life (p value −0.00). The minimum expected increment in life expectancy for taking palliative chemotherapy was ">1 year" in 190 patients (94.5%; 95% CI 91.5–97.7%). Conclusion: The primary expectation from palliative chemotherapy in head and neck cancer patients is not necessarily living longer in all patients. The magnitude of benefit preferred by the patients from chemotherapy far exceeded the current standards for drug approval.